DAMPAK TEKNOLOGI INFORMASI TERHADAP BIAYA - Handayani, Fitri (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2021)
Information technology has grown very rapidly. Information technology cannot live with human life. Almost in every sphere of life requires information technology. Information technology has contributed to the development of business. The sophistication of information technology provides ease in the operational phase of the company where all activities will be stored in the system. This will create operational operational costs. Ease in accessing the internet will facilitate customers in finding the products they want automatically and will make customers interested in the services to be offered company.